Feeding Harvesters in the Mid-Eighteenth Century - Thick, Malcolm (Petits Propos Culinaires, 2018)
Little has been written by historians on food provided for harvest workers in England. Christopher Dyer, in 1988, used medieval manorial records to examine changes in diet in the late Middle Ages but he did so in terms of food acquired by manors to feed workers, not the actual meals they consumed. E.J.T. Collins in 1976 examined migrant labour in British agriculture in the nineteenth century but was not concerned with food consumed. David Hoseason’s book on the nineteenth century agricultural worker has little in it on harvest food. Other writers of food history have simply used information extracted and summarized from William Ellis (as I did in my introduction to 2000 edition of Ellis’s The Country Housewife’s Family Companion of 1750). Ellis stands out as the only writer, in the eighteenth or almost any other century, who tells us what exactly harvesters were fed, on a meal by meal basis and how he, and his Hertfordshire farmer neighbours (or rather their wives), conducted this victualling. This paper will examine closely what he had to say on the subject and seek corroboration from other sources of Ellis’s information on harvest food.